Poorer nations turn to publicly developed GM crops - Cohen, Joel I. (Springer, 2005)
This paper presents the results of a study that explored the current state of research, regulation, genetic resources and institutional roles in developing GM crops. The study surveyed GM research on 45 different crops, conducted at 61 public research institutes in 15 developing economies. The author finds that whilst genetically modified crops are often framed as the products of multinational corporations, in poorer nations it is often public research that is vibrant and attempting their development. Often this research draws upon indigenous plant varieties to cultivate improved crops for local use by small-scale farmers.